Management Planning Strategy for PAUD Institutions at TKN Pembina, Sebangau District, Palangka Raya City - Vira Ezha; Fetriani; Linda Susanti; Nopraeda; Yoan Colina (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
The increase in the number of early childhood education units must be balanced with good governance to realize a golden generation of Indonesia. With good governance to realize the golden generation of Indonesia that fulfills the constitution. Early childhood education now requires new steps and paradigms, including aspects of planning and management. The purpose of this research is to analyze the planning stages of PAUD institution management in TKN Pembina Kec. Sebangau, which supports the development of quality national education. This research uses descriptive qualitative research methods with this type of research is phenomenology with data collection techniques Observation, Interview and Documentation. Based on the results of research conducted at TKN Pembina Kec. Sebangau, it shows that the management planning strategy of PAUD institutions is carried out referring to the direction of PAUD management planning. Strategic planning of early childhood education management can be done for example through identification of needs and problems, environmental studies, determination of vision and mission, preparation of programs, and preparation of documents and plans.